Rebellion, rascals, and revenue tax follies and wisdom through the ages - Michael Keen, Joel Slemrod (Princeton Princeton University Press, 2021)
Governments have always struggled to tax in ways that are effective and tolerably fair. Sometimes they fail grotesquely, as when, in 1898, the British ignited a rebellion in Sierra Leone by imposing a tax on huts - and, in repressing it, ended up burning the very huts they intended to tax. Sometimes they succeed astonishingly, as when, in 18th-century Britain, a cut in the tax on tea massively increased revenue. In this entertaining book, two leading authorities on taxation, Michael Keen and Joel Slemrod, provide a fascinating and informative tour through these and many other episodes in tax history, both preposterous and dramatic - from the plundering described by Herodotus and an Incan tax payable in lice to the (misremembered) Boston Tea Party and the scandals of the Panama Papers. Along the way, listeners meet a colorful cast of tax rascals, and even a few tax heroes.
Includes index
Keywords: Taxation-history